Anatomy and Physiology of the Circulatory and Ventilatory Systems - Thiriet, Marc.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Together, the volumes in this series present all of the data needed at various length scales for a multidisciplinary approach to modeling and simulation of flows in the cardiovascular and ventilatory systems, especially multiscale modeling and coupled simulations. The cardiovascular and respiratory systems are tightly coupled, as their primary function is to supply oxygen to, and remove carbon dioxide from, the body's cells. Because physiological conduits have deformable and reactive walls, macroscopic flow behavior and prediction must be coupled to nano- and microscopic events in a corrector scheme of regulated mechanism. Therefore, investigation of flows of blood and air in physiological conduits requires an understanding of the biology, chemistry, and physics of these systems, together with the mathematical tools to describe their functioning in quantitative terms. The present volume focuses on macroscopic aspects of the cardiovascular and respiratory systems in normal conditions, i.e., anatomy and physiology, as well as the acquisition and processing of medical images and physiological signals. Reviews the anatomy and physiology of blood circulation and the body's ventilation Reviews biological data for a better understanding of macroscopic scale processes Describes the signals and images that are used to explore system function and as input data for computations
Preface -- Chapter 1: Anatomy of the Cardiovascular Apparatus -- Chapter 2: Anatomy of the Ventilatory Apparatus -- Chapter 3: Cardiovascular Physiology -- Chapter 4: Physiology of Ventilation -- Chapter 5: Medical Images and Physiological Signals -- Conclusions -- References -- List of Currently Used Prefixes and Suffixes -- List of Aliases and Primary Symbols -- Complementary Lists of Notations -- Index.
Keywords: Physics; Cardiology; Biological models; Hydraulic engineering; Biomedical engineering; Physics; Biophysics and Biological Physics; Biomedical Engineering; Mathematical and Computational Biology; Systems Biology; Engineering Fluid Dynamics; Cardiology